Influence of temperature and substrate composition on anaerobic biogas production in a pilot-scale reactor - Balasubramanian K; Sivakumar K (Renewable Energy and Sustainable Development, 2024)
The research investigates how temperature and substrate composition impact anaerobic biogas production in a pilot-scale reactor. Anaerobic digestion is a vital process for converting organic substrates into biogas, mainly composed of methane and carbon dioxide. Temperature plays a crucial role in influencing this process. The experiment was conducted under mesophilic (35°C), thermophilic (55°C), and hyper thermophilic (80°C) conditions, using a pilot-scale reactor with a capacity of 50 liters and an effective volume of 40 liters. Key parameters, including biogas production, carbon and nitrogen content, carbon-to-nitrogen (C:N) ratios, pH levels, and biomass concentrations, were monitored throughout a 60-day operational period. The highest biogas production, reaching 6398 ml/d, occurred under mesophilic conditions. Scanning electron microscopy (SEM) and phylogenetic analysis were performed, revealing the presence of Methanococcus aeolicus species in the treated sludge.   Received: 25 June 2024 Accepted: 31 July 2024 Published: 25 August 2024